2016
DOI: 10.3329/jesnr.v8i2.26858
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tidal Events on the Water Quality in the Merbok Estuary, Kedah, Malaysia

Abstract: This study was carried out to observe effects of tidal events on the water quality parameters at Merbok estuary, Kedah, Malaysia. Twenty four hours sampling were conducted at Station 1, 2 and 3 from 12 th November (spring tide) to 3 rd December (neap tide) 2011 on weekly interval. Results showed that water quality parameters varied with the following ranges: temperature (26.10 -30.7°C), pH (6.29 -7.22), dissolved oxygen (0.65 -5.48 mgL -1 ), salinity (0.50 -35PSU), nitrate (0.037 -0.647mgL -1 ), nitrite (0.09 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 13 publications
5
11
0
Order By: Relevance
“…The concentration of salinity indicates an increase from the early stage to the later. As reported by Fatema et al (2016), the water quality parameters, including salinity were significantly different between spring and neap tide events. This findings also aligned with studies by Uncles and Stephens (2011) and Purnaini, Sudarmadji and Purwono (2018).…”
Section: Salinity Variability Maps For Season 1 and Season 2 2019supporting
confidence: 59%
See 1 more Smart Citation
“…The concentration of salinity indicates an increase from the early stage to the later. As reported by Fatema et al (2016), the water quality parameters, including salinity were significantly different between spring and neap tide events. This findings also aligned with studies by Uncles and Stephens (2011) and Purnaini, Sudarmadji and Purwono (2018).…”
Section: Salinity Variability Maps For Season 1 and Season 2 2019supporting
confidence: 59%
“…However, when heavy rains and high tides occur, the possibility for seawater to enter the river is very high due to rising sea levels. That is caused by the concentration of salinity is higher in this area (Fatema, Omar, & Isa, 2016). In addition, during this period, the river is used directly for the purpose of irrigating rice plants in the area.…”
Section: Salinity Variability Maps For Season 1 and Season 2 2019mentioning
confidence: 93%
“…In addition, the river absorbs heat from the tides flowing in from the sea. The inflow of sea water from downstream to upstream causes the water temperature to rise at high tide ( Fatema et al . 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the tidal regime also aff ects the movement of pollutants and the dispersion of pollutants from diff erent discharge points (Kar et al, 2022). Fatema et al (2015) suggested that tidal activity has changed the temperature, salinity, pH, dissolved oxygen, nitrogen and phosphate in the river water environment.…”
Section: Introductionmentioning
confidence: 99%